Nylon 6 nanocomposites prepared by a melt mixing masterbatch process - Shah, R.K.; Paul, D.R.
A melt mixing masterbatch process for preparing nylon 6 nanocomposites that provides good exfoliation and low melt viscosities has been investigated. It is known that high molecular weight (HMW)grades of nylon 6 lead to higher levels of exfoliation of organoclays than do low molecular weight (LMW)grades of nylon 6. However, LMW grades of nylon 6 have lower melt viscosities, which are favorable for certain commercial applications like injection molding. To resolve this, a two-step process to prepare nanocomposites based on nylon 6 is explored here. In the first step, a masterbatch of organoclay in HMW nylon 6 is prepared by melt processing to give exfoliation. In the second step, the masterbatch is diluted with LMW nylon 6 to the desired montmorillonite (MMT)content to reduce melt viscosity. Wide angle X-ray scattering, transmission electron microscopy, and stress-strain analysis were used to evaluate the effect of the clay content in the masterbatch on the morphology and physical properties of the final nanocomposite. The melt viscosity was characterized by Brabender Torque Rheometry. The physical properties of the nanocomposites prepared by the masterbatch approach lie between those of the corresponding composites prepared directly from HMW nylon 6 and LMW nylon 6. A clear trade-off was observed between the modulus and melt processability. Masterbatches that have lower MMT content offer a significant decrease in melt viscosity and a small reduction in modulus compared to nanocomposites prepared directly from HMW nylon 6. Higher MMT concentrations in the masterbatch lead to a less favorable trade-off.
Keywords: NYLON 6; NANOCOMPOSITES; MASTERBATCH